Specificity and immunosuppression of human cytotoxic T lymphocyte responses to herpes simplex virus - Posavad, Marie Christine (My University, 1993)
Cytotoxic T lymphocytes (CTL) are important in controlling a number of viral infections including those caused by members of the herpesvirus family. Many studies have focussed on the phenotype of human CTL specific for herpes simplex virus (HSV) although few studies address their specificity. HSV glycoproteins B (gB) and D (gD) can serve as target antigens for CD4⁺ and CD8⁺ anti-HSV CTL clones generated by repeated stimulation of peripheral blood mononuclear cells (PBMC) with HSV antigens or HSV-infected cells. In the present study, the presence of gB- and gD-specific CTL in polyclonal cultures of anti-HSV CTL stimulated with a single in vitro exposure to HSV-1 was examined using autologous EBV-transformed B-lymphoblastoid cell lines (LCL) infected with recombinant vaccinia virus or adenovirus vectors encoding gB (vgB11, AdgB) or gD (vgD52, AdgD). Of six HSV seropositive donors tested, only one individual generated CD4⁺ and CD8⁺ T cells capable of lysing LCL infected with HSV, vgB11 or vgD52. Anti-HSV CTL from the remaining five HSV seropositive donors lysed HSV-infected LCL only. Therefore, gB and gD can serve as target antigens for polyclonal cultures of human anti-HSV CTL although the majority of the bulk CTL response in most patients is directed at HSV antigens other than gB and gD. LCL infected with recombinant adenoviruses were not recognized by gB- and gD-specific CTL due to the restricted expression of the inserted gene product. Since LCL infected with recombinant adenoviruses were not lysed by human anti-HSV CTL, human fibroblasts, which are permissive to adenovirus infection, were chosen as potential target cells. However, human fibroblasts infected with HSV-1 (HSV-FB) were not lysed by human anti-HSV CTL or human allo-antigen specific CTL (allo-CTL). HSV-FB were not only resistant to lysis by human CTL, but exposure of CTL to HSV-FB rendered the CTL unable to lyse its normally sensitive target cell. Studies concerning the mechanism of this inhibition suggested that there were two distinct mechanisms of inhibition of CTL lysis. The first involved FB infected with HSV-1 for 2 hours and required the expression of ICP4, an immediate-early protein of HSV-1, but not infectious virus or virus-induced shut-off of host protein synthesis. The second mechanism of inhibition occurred later in the HSV replication cycle and involved the infection of CTL via cell-to-cell spread of HSV-1 from FB infected for 20 hours. The elucidation of mechanisms involved in HSV-induced immunosuppression may foster the development of preventative or therapeutic strategies aimed at controlling these pathogens in humans.
Keywords: Medical Sciences; Medical Sciences